Reactive Oxygen Species, a Potential Therapeutic Target for Vascular Dementia - Amanda Louise White; Grant M. Talkington; Blake Ouvrier; Saifudeen Ismael; Rebecca J. Solch-Ottaiano; Gregory Bix (Biomolecules)
Vascular dementia (VaD) is a progressive neurodegenerative condition prevalent among elderly adults marked by cognitive decline resulting from injured and/or improperly functioning cerebrovasculature with resultant disruptions in cerebral blood flow. Currently, VaD has no specific therapeutics and the exact pathobiology is still being investigated. VaD has been shown to develop when reactive oxygen species (ROS) form from damaged targets at different levels of organization—mitochondria, endothelial cells, or cerebrovasculature. In this review, we highlight how specific ROS molecules may be important in the development of VaD and how they can be targeted as a potential therapeutic for VaD.